"The way the country has been carved up by researchers": ethics and power in north–south public health research. Issue 1 (December 2016) - Walsh, Aisling; Brugha, Ruairi; Byrne, Elaine
Abstract Background Despite the recognition of power as being central to health research collaborations between high income countries and low and middle income countries, there has been insufficient detailed analysis of power within these partnerships. The politics of research in the global south is often considered outside of the remit of research ethics. This article reports on an analysis of power in north–south public health research, using Zambia as a case study. Methods Primary data were collected in 2011/2012, through 53 in-depth interviews with: Zambian researchers (n =  20), Zambian national stakeholders (n =  8) and northern researchers who had been involved in public health research collaborations involving Zambia and the global north (n =  25). Thematic analysis, utilising a situated ethics perspective, was undertaken usingNvivo 10 . Results Most interviewees perceived roles and relationships to be inequitable with power remaining with the north. Concepts from Bourdieu's theory of Power and Practice highlight new aspects of research ethics:Northern and southern researchers perceive that differenthabituses exist, north and south -habituses of domination (northern) and subordination (Zambian) in relation to researcher relationships. Bourdieu'shysteresis effect provides a possible explanation for why power differentials continue to exist. In some cases, new opportunities have arisen for Zambian researchers; however, they may not immediately recognise and grasp them. Bourdieu's concept ofCapitals offers an explanation of how diverse resources are used to explain these power imbalances, where northern researchers are often in possession of more economic, symbolic and social capital; while Zambian researchers possess more cultural capital. Conclusions Inequities and power imbalances need to be recognised and addressed in research partnerships. A situated ethics approach is central in understanding this relationship in north–south public health research.